213k views
5 votes
Find the inverse function of F(x) = 1/2x-6​

User HBCondo
by
5.3k points

2 Answers

2 votes

Answer:


F^(-1) (x) = 2x + 12

Explanation:

Let's assume F(x) = y, then


y = (1)/(2) x - 6

Let us solve the equation for x.


y + 6 = (1)/(2) x


2y + 12 = x

Next, replace y with x and also replace x with F⁻¹(x)

Answer:
F^(-1) (x) = 2x + 12

User Eponymous
by
4.9k points
0 votes
F^-1 (x) = 2x + 12 hope it help
User Robin Luiten
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.